Exemplary Damages: Two Commonwealth Cases - PHANG, Andrew (Institutional Knowledge at Singapore Management University, 2003)
The topic of exemplary damages has often been shrouded in controversy. Indeed, in some jurisdictions (such as England), the very award of such damages is confined to an extremely narrow compass (though cf. the recent House of Lords decision in Kuddus v. Chief Constable of Leicestershire Constabulary [2001] UKHL 29, [2002] 2 A.C. 122). Although the jurisdiction to award such damages is broader in other Commonwealth jurisdictions, difficult issues remain, two of which were recently explored by the highest appellate courts in New Zealand and Canada, respectively.